Plasma biomarkers for diagnosis of Alzheimer's disease and prediction of cognitive decline in individuals with mild cognitive impairment - Kivisäkk, Pia; Carlyle, Becky C.; Sweeney, Thadryan; Trombetta, Bianca A.; LaCasse, Kathryn; El-Mufti, Leena; Tuncali, Idil; Chibnik, Lori B.; Das, Sudeshna; Scherzer, Clemens R.; Johnson, Keith A.; Dickerson, Bradford C.; et al. (Frontiers in Neurology, 2023)
Background: The last few years have seen major advances in blood biomarkers for Alzheimer’s Disease (AD) with the development of ultrasensitive immunoassays, promising to transform how we diagnose, prognose, and track progression of neurodegenerative dementias. Methods: We evaluated a panel of four novel ultrasensitive electrochemiluminescence (ECL) immunoassays against presumed CNS derived proteins of interest in AD in plasma [phosphorylated-Tau181 (pTau181), total Tau (tTau), neurofilament light (NfL), and glial fibrillary acidic protein (GFAP)]. Two sets of banked plasma samples from the Massachusetts Alzheimer’s Disease Research Center’s longitudinal cohort study were examined: A longitudinal prognostic sample (n=85) consisting of individuals with mild cognitive impairment (MCI) and 4 years of follow-up and a cross-sectional sample (n=238) consisting of individuals with AD, other neurodegenerative diseases (OND), and normal cognition (CN). Results: Participants with MCI who progressed to dementia due to probable AD during follow-up had higher baseline plasma concentrations of pTau181, NfL, and GFAP compared to non-progressors. The best prognostic discrimination was observed with pTau181 (AUC=0.83, 1.7-fold increase) and GFAP (AUC=0.83, 1.6-fold increase). Participants with autopsy- and/or biomarker verified AD had higher plasma levels of pTau181, tTau and GFAP compared to CN and OND, while NfL was elevated in AD and further increased in OND. The best diagnostic discrimination was observed with pTau181 (AD vs CN: AUC=0.90, 2-fold increase; AD vs OND: AUC=0.84, 1.5-fold increase) but tTau, NfL, and GFAP also showed good discrimination between AD and CN (AUC=0.81-0.85; 1.5-2.2 fold increase). Conclusions: These new ultrasensitive ECL plasma assays for pTau181, tTau, NfL, and GFAP demonstrated diagnostic utility for detection of AD. Moreover, the absolute baseline plasma levels of pTau181 and GFAP reflect cognitive decline over the next 4 years, providing prognostic information that may have utility in both clinical practice and clinical trial populations.